قرآنِ مجید میں مجازکااستمعال:تحقیقی و تجزیاتی مطالعہ: Figurative Language in the Holy Qur’an: A Critical and Analytical Study (Al-Qamar, 2025)
This study presents a comprehensive analytical examination of figurative language (majāz) in the Holy Qur’an, exploring its conceptual, linguistic, and rhetorical dimensions. The research investigates how figurative expressions enhance the Qur’anic discourse, deepen meaning, and enrich interpretive possibilities. It highlights the principles adopted by classical and modern scholars regarding the acceptance, scope, and application of majāz in Qur’anic exegesis. The study also evaluates the semantic, stylistic, and contextual factors that guide the identification of figurative usage in the Qur’an. By comparing literal and non-literal interpretations, it sheds light on the exegetical implications that arise from adopting a figurative approach. The analysis demonstrates that majāz serves as a powerful linguistic tool that conveys complex spiritual and moral concepts with clarity and eloquence. Additionally, the research underscores the importance of understanding figurative language for accurate tafsīr and avoidance of interpretive rigidity. Overall, this study contributes to a deeper appreciation of the Qur’an’s linguistic richness and its dynamic rhetorical features.
Keywords: Figurative language in the Qur’an, rhetorical analysis of majāz, semantic and contextual interpretation, classical and modern exegetical perspectives